EVOLUTION OF YURY DUD: FROM A POPULAR VIDEO BLOGGER TO A PUBLIC FIGURE / ЭВОЛЮЦИЯ ЮРИЯ ДУДЯ: ОТ ПОПУЛЯРНОГО ВИДЕОБЛОГЕРА ДО ОБЩЕСТВЕННОГО ДЕЯТЕЛЯ - PODOSOKORSKY NIKOLAY N. / ПОДОСОКОРСКИЙ НИКОЛАЙ НИКОЛАЕВИЧ (Наука телевидения)
This article continues the research, which started in 2018, and examines the evolution of Yury Dud, one of the most popular bloggers and journalists in modern Russia, over the past two years. In 2018–2020, he released several educational documentaries (about the Stalinist repressions and Kolyma, the Beslan tragedy of 2004, the HIV epidemic in Russia, Silicon Valley startups, the disabled and the homeless, etc.). The documentaries drew a huge response, turning Yury into a public figure with significant political potential. According to sociological surveys conducted in the spring of 2020, Dud was named one of the living figures who inspire Russians the most (the audience most interested in him is young people between 18 and 24 years old). The text demonstrates the tremendous influence of the blogger’s talk show on the moods and actions of his viewers, and the way it changes their lives. As of December 2020, Yury Dud has almost 15 million subscribers on his social media accounts and more than 1.2 billion views on his YouTube channel alone. His success is based on the competent use of new media tools for promotion of a personal brand and his virtuoso ability to reach out to a variety of audiences (differing in age, education, income level, locations, interests, etc.), which normally do not overlap. Thus, his enlightenment works in several directions: not only he introduces the mass audience to new information in a fascinating way, but also helps different circles to better understand each other.